PENGEMBANGAN MEDIA VIDEO ANIMASI BERSASIS MODEL SEQUENCED DI KELAS IV SEKOLAH DASAR - Cicilia Ovavia; Marlina; Desyandri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This research was conducted based on the observation results and the researchers’ experience that integrated thematic learning at grade IV of elementary schools, especially in two subjects: IPS and PKn, which linked one another. This research was conducted at UPT SDN 08 Mandeh for as many as 28 students in grade IV. This study aimed to produce and reveal the successful use of animation media using the Sequenced model in integrated learning in grade IV elementary schools. This media was applied for social sciences and civics learning. This study utilized the Sequenced model, including several stages, namely: (1) sequence, (2) series, or (3) series. With limited articulation across disciplines, teachers could rearrange the order of topics so that similar units could intersect. Two related disciplines were sequenced so that the content of the two subjects could be taught in parallel. By ordering the topics, the activities of each of these disciplines could improve one another. This study was research and development. After the production stage, the initial product was produced and validated by a content expert, learning design expert, and instructional media expert. Furthermore, the product was tested on students through three stages: individual trials, small group trials, and field trials. This research concluded that the animation video learning media is expertly validated and attractive